Atividade antimicrobiana do óleo de pequi (Caryocar brasiliense) e do óleo essencial de cravo-da-índia (Syzygium aromaticum) frente a isolados de Pseudomonas aeruginosa de otite canina - Costa, Larissa Vieira (2022)
Pseudomonas aeruginosa is an opportunistic Gram-negative bacterium and its increasing resistance is a global threat to public health. It is commonly identified in difficult-to-treat canine otitis media such as severe nosocomial infections. In this scenario, there is a need to search for therapeutic alternatives to the uses of antimicrobials and, in this context, herbal medicines are known for their various biological activities, including their antimicrobial action. The objective of this research was to evaluate the antibacterial effect of clove essential oil and pequi vegetable oil against P. aeruginosa isolates from canine otitis, as well as their resistance profile. 41 P. aeruginosa isolates were evaluated and 20 antibiotics were tested, highlighting the high resistance to beta-lactams including carbapenems. Of these, 97.56% (40/41) of the isolates were classified as multidrug-resistant. The antimicrobial efficacy of clove oil was evaluated by the microdilution method and compared with gentamicin. The minimal inhibitory (MIC) and minimal bactericidal (MBC) concentrations were similar and ranged between 3.26mg/mL and 6.53mg/mL. It was not possible to perform the MIC of pequi oil. In view of these results, it was concluded that clove essential oil has been shown to have antimicrobial action against multidrug-resistant P. aeruginosa isolates, which provides a natural alternative to the use of antimicrobials.